Isolation and characterization of porcine epidemic diarrhea virus with a novel continuous mutation in the S10 domain - Han, Xueying; Liu, Yangkun; Wang, Yan; Wang, Tiejun; Li, Ning; Hao, Feng; Yao, Lunguang; Guo, Kangkang (Frontiers in Microbiology, 2023)
Porcine epidemic diarrhea virus (PEDV), which re-emerged in China in 2010, has caused severe economic losses to the global pig industry. In this study, a PEDV strain, designated PEDV WMB, was isolated from piglets with severe diarrhea on a pig farm in Henan Province of China. Whole-genome sequencing and analysis revealed that the PEDV WMB strain belongs to subtype G2c and has a unique continuous mutation in the S10 antigenic epitope of the S protein. Moreover, the virus-neutralization (VN) test indicated that polyclonal antibodies against the S10 protein of other G1 and G2 strains showed reduced VN reactivity to PEDV WMB. The pathogenicity of PEDV WMB was further investigated in 3-day-old piglets. PEDV infection-related clinical symptoms and morphological lesions were observed and confirmed by histopathological and immunohistochemical examination (IHC). These results illustrated that continuous mutation of the S10 epitope might affect the immunogenicity or pathogenicity of PEDV, providing evidence of the need to monitor the genetic diversity of the virus and develop effective measures to prevent and control PEDV.